Variability in Single Digit Addition Problem-Solving Speed Over Time Identifies Typical, Delay and Deficit Math Pathways - Reeve, Robert A.; Gray, Sarah A.; Butterworth, Brian L.; Paul, Jacob M. (Frontiers in Psychology, 2018)
One hundred sixty-four children completed a 12-item single digit addition (SDA) test on four occasions over a six year period. We also assessed (1) children’s digit span, visuospatial working memory, and non-verbal IQ, and (2) the speed with which they named single numbers and letters and arrays of one to three dots. The latter measure assessed subitizing ability. Children completed a double-digit mental addition test at the end of the study. We conducted a latent profile analysis to determine if there were different SDA problem solving response time (PRT) variability patterns across the four test occasions, which yielded three distinct PRT variability patterns. In one, labelled a typical acquisition pathway, mean PRTs were relatively low and PRT variability diminished over time. In a second pathway, label a delayed pathway, mean PRT and variability was high initially but diminished over time. In the third, a deficit pathway, mean PRT and variability remained relatively high throughout the years of the study. We investigated the degree to which the three SDA PRT variability pathways were associated with (1) different cognitive ability measures, and (2) double-digit mental addition abilities. The deficit pathway differed from the typical and delayed pathway on the subitizing measure only, but not other measures; and the latter two pathways also differed from each other on the subitizing but not other measures. Double-digit mental addition problem solving success differed between each of the three pathways, and mean PRT variability differed between the typical and the delayed and deficit pathways. The latter two pathways did not differ from each other. The findings emphasize the value of examining individual differences in problem-solving PRT variability longitudinally as an index of math ability, and highlight the important of subitizing ability as a diagnostic index of math ability/difficulties.